Peripheral Blood‐Derived Mesenchymal Stem Cells: Candidate Cells Responsible for Healing Critical‐Sized Calvarial Bone Defects. (5th March 2015) - Li, Shaowei; Huang, Ke-Jung; Wu, Jen-Chieh; Hu, Michael S.; Sanyal, Mrinmoy; Hu, Min; Longaker, Michael T.; Lorenz, H. Peter
Abstract : A coculture system that routinely produces a group of cells from adult peripheral blood is presented. A subset of CD45 − cells with a fibroblastic morphology was isolated. The CD45 − fibroblastic cells are the first peripheral blood‐derived cells that fulfill the criteria of mesenchymal stem cells as defined by the International Society for Cellular Therapy. Abstract : Postnatal tissue‐specific stem/progenitor cells hold great promise to enhance repair of damaged tissues. Many of these cells are retrieved from bone marrow or adipose tissue via invasive procedures. Peripheral blood is an ideal alternative source for the stem/progenitor cells because of its ease of retrieval. We present a coculture system that routinely produces a group of cells from adult peripheral blood. Treatment with these cells enhanced healing of critical‐size bone defects in the mouse calvarium, a proof of principle that peripheral blood‐derived cells can be used to heal bone defects. From these cells, we isolated a subset of CD45 − cells with a fibroblastic morphology. The CD45 − cells were responsible for most of the differentiation‐induced calcification activity and were most likely responsible for the enhanced healing process. These CD45 − fibroblastic cells are plastic‐adherent and exhibit a surface marker profile negative for CD34, CD19, CD11b, lineage, and c‐kit and positive for stem cell antigen 1, CD73, CD44, CD90.1, CD29, CD105, CD106, and CD140α. Furthermore, these cells exhibited osteogenesis, chondrogenesis, and adipogenesis capabilities. The CD45 − fibroblastic cells are the first peripheral blood‐derived cells that fulfill the criteria of mesenchymal stem cells as defined by the International Society for Cellular Therapy. We have named these cells "blood‐derived mesenchymal stem cells."